FAKE NEWS AND THE GEOGRAPHY OF THE ROMANIAN INDUSTRY (PANGEEA, 2025)
This study analyzes the impact of several groups posts on social network, wich are aimed at focusing on the Romanian industry. After the extended 3-month study, we found that most of the posts were aimed at distorting the facts about the Romanian industry and economy.
Keywords: disinformation; industry; Romania; social networks